Genetic manipulation of the interconversion between diacylglycerols and triacylglycerols in Rhodosporidium toruloides - Zhang, Yue; Zhang, Sufang; Chu, Yadong; Zhang, Qi; Zhou, Renhui; Yu, Di; Wang, Shuang; Lyu, Liting; Xu, Guowang; Zhao, Zongbao Kent (Frontiers in Bioengineering and Biotechnology, 2022)
The basidiomycetous yeast Rhodosporidium toruloides (R. toruloides) is an excellent producer for neutral lipids, including triacylglycerols (TAG). Partially because genetic tools for this yeast were less developed, limited efforts were shown to explore its capacity for the production of higher-value lipids such as diacylglycerols (DAG). Here, four genes linked to the interconversion between DAG and TAG were manipulated to promote the production of DAG and free fatty acids (FFA). Among them, three TAG synthesis-related genes, DGA1, LRO1, and ARE1, were down-regulated successively via the RNA interference technology, and an endogenous TAG lipase encoded by TGL5 was fused with LDP1 and over-expressed to convert TAG into DAG and FFA. Results showed that those engineered R. toruloides strains grew normally under nutrient-rich conditions but notably slower than the parental strain NP11 in the lipid production stage. When cultivated in nitrogen-limited media, engineered strains were able to produce total lipids with improved contents of DAG and FFA by up to two-fold and three-fold, respectively. Further correlation analysis between lipid composition and cell density indicated that the formation of TAG correlated positively with cell growth; however, other lipids including DAG did negatively. This study offered valuable information and strains to engineer R. toruloides for advanced production of fatty acid derivatives